Design and Build Detector and Overcome LPG Gas Leakage Based TGS2610 Sensor - Rida Angga Kusuma (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2013)
In this research has designed LPG leak gas detection system along with to overcome that works automatically. The mechanic system will open stem in the gas regulator when the sensor detecting of LPG gas leakage around the gas source with a loud alarm sound, so the incidence of accidental explosions and fires can be avoided. Sensor is used in the design of this research using TGS2610 type which of LPG gas detection system is based on comparison of the output voltage from the gas sensorto the gas levels on the air. The Mechanic system is used to move the gas regulator stem is a servo motor that spins in control with a certain pulse, so when installing and removing the gas regulator can be done with a single button from control panel. The LPG gas detection system is equipped with a battery backup so in case of electric outages from PLN the circuit will keep work fine.With a mechanical design that has been designed, the gas regulator can be replaced easily by the size of the general market.